TAHUN PELAJARAN 2017/2018 PENGGUNAAN MEDIA GAMBAR SERI UNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGAN SEDERHANA DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SD ISLAM NU PUNGKURAN - Istiqomah, Nur; Karim, Abdul (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Indonesian Language Learning in SD focuses on language skills. Writing whichis one aspect of language as if a constraint for most elementary school children.Though writing skills for elementary school children should be given early on.Based on the reflection of learning in Islamic Elementary School NUPungkuran, the result of learning to write in general, with simple essay materialin particular, many students still can not meet the KKM. For that done researchby applying the image series media. The purpose of this study is to improve student learning outcomes in writing simple essay class V semester I SD IslamicNU Pungkuran. This research is conducted in two cycle of improvement, eachcycle is done with four stages of planning, implementation, observation, andreflection. The subjects of this research are teachers and students of grade V SDIslam NU Pungkuran.Teknik data analysis using qualitative data analysis techniques. The results showed that the percentage of learning masteryincreased in each cycle, the cycle I is 70% and in cycle II is 100% already meetthe KKM. The conclusion of this research is the series picture media was ableto improve the ability to write simple essay Indonesian class V student Islam SDNU Pungkuran first semester of academic year 2017/2018.Keywords: Language Indonesia, Writing, and Drawing Series